2011
DOI: 10.3897/phytokeys.2.730
|View full text |Cite
|
Sign up to set email alerts
|

Lectotypifications, synonymy, and a new name in Capsicum (Solanoideae, Solanaceae)

Abstract: Considerable confusion exists within Capsicum (Solanaceae) regarding the status and typification of several names, in part due to misidentifications. Some types were destroyed in Berlin during the Second World War, some have not been found by modern systematics, while others exhibit uncertain locality data or contain material from more than one species. Fourteen lectotypes, synonyms, and a new name, Capsicum eshbaughii Barboza nom. nov.,are proposed here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…Progress has been made in the delimitation of some species, the addition of new species (Baral and Bosland, 2004;Barboza, 2011;Barboza and Bianchetti, 2005;Barboza et al, 2011;Bosland and Gonz alez, 2000;Carrizo García et al, 2013;Nee et al, 2006), and the clarification of some nomenclatural problems (Barboza, 2011;Knapp et al, 2015). Molecular phylogenetic analyses have contributed to the understanding of species relationships (Jarret and Dang, 2004;Walsh and Hoot, 2001).…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…Progress has been made in the delimitation of some species, the addition of new species (Baral and Bosland, 2004;Barboza, 2011;Barboza and Bianchetti, 2005;Barboza et al, 2011;Bosland and Gonz alez, 2000;Carrizo García et al, 2013;Nee et al, 2006), and the clarification of some nomenclatural problems (Barboza, 2011;Knapp et al, 2015). Molecular phylogenetic analyses have contributed to the understanding of species relationships (Jarret and Dang, 2004;Walsh and Hoot, 2001).…”
Section: Taxonomymentioning
confidence: 99%
“…Similarly, in the cultivar Belize Sweet, the presence of a 5-bp insertion (TGGGC) in the pAmt gene led to a frameshift mutation that inhibited capsaicinoid biosynthesis (Tanaka et al, 2010b). Park et al (2015) reported a 12-bp deletion (TCTGCTGGTCTC) in exon seven, and a SNP in exon 14 Barboza, 2011;Barboza and Bianchetti, 2005;Barboza et al, 2011;Bianchetti 1996;Bianchetti et al, 1999;Moscone et al, 2007;Nee et al, 2006;Pozzobon et al, 2006. y Scaldaferro et al, 2006Scaldaferro et al, , 2016 x # = synteny of 5S and 45S sites; p = short arm, q = long arm. w Moscone et al, 2003. v Belletti et al, 1998. u This publication.…”
Section: Capsaicinoids: the ''Heat''mentioning
confidence: 99%
“…Capsicum L. Is a genus of approximately 32 species [61]; however, with new species being named on a regular basis, this number is likely to exceed 40 in the near future. Comprising small to robust shrubs, some with a climber-like habit.…”
Section: Tribe Capsiceae D'arcymentioning
confidence: 99%
“…As outlined above, the pungent (hot) flavor of chili fruit is due to capsaicinoids, which are produced exclusively in this genus (Levey et al 2007). In addition to capsaicinoids, chilies are also defended by other chemical (Harborne 1986;Andersson 1999) and structural traits (Drummond 1986;Barboza 2011), which likely play adaptive defensive roles. However, of these defenses, the ecological significance of pungency is currently the best understood so we focus on it here.…”
Section: Ecological Importance Of Natural Defense Trait Differentiationmentioning
confidence: 99%